2018
DOI: 10.1002/ange.201808085
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic versus Electrophilic Reactivity of Bioinspired Superoxido Nickel(II) Complexes

Abstract: The formation and detailed spectroscopic characterization of the first biuret‐containing monoanionic superoxido‐NiII intermediate [LNiO2]− as the Li salt [2; L=MeN[C(=O)NAr)2; Ar=2,6‐iPr2C6H3)] is reported. It results from oxidation of the corresponding [Li(thf)3]2[LNiIIBr2] complex M with excess H2O2 in the presence of Et3N. The [LNiO2]− core of 2 shows an unprecedented nucleophilic reactivity in the oxidative deformylation of aldehydes, in stark contrast to the electrophilic character of the previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…The Mulliken spin distribution was calculated to be localized on O 2 adduct by 0.97e (Figure 3b). This correlates well with an experimental value (0.87e) that was predicted by the 17 21 This spectral feature correlates well with that observed in the present study; their interpretations are not inconsistent with our assignment.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The Mulliken spin distribution was calculated to be localized on O 2 adduct by 0.97e (Figure 3b). This correlates well with an experimental value (0.87e) that was predicted by the 17 21 This spectral feature correlates well with that observed in the present study; their interpretations are not inconsistent with our assignment.…”
Section: Resultssupporting
confidence: 92%
“…Taking account of reaction , we can assign the bands at 8328.7 and 8332.2 eV to transitions of the T-shaped Ni I –carbonyl site, whereas the bands at 8329.6 and 8335.8 eV are assigned as the transitions of the square planar Ni II –superoxo site. It was reported that the β-diketiminate Ni II –superoxo complex shows a pre-edge peak at 8333.2 eV and an additional peak at 8338.5 eV . This spectral feature correlates well with that observed in the present study; their interpretations are not inconsistent with our assignment.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…191 Nucleophilic deformylation of aldehydes has also been reported for a monoanionic nickel(II)-superoxo intermediate, [Ni II O2(L)]  , L= MeN{C(=O)NAr}2; Ar= 2,6-iPr2C6H3]. 192 Cho and co-workers have synthesized a nickel(III)-peroxo complex with the Me6trien ligand, which is an analogue of the macrocyclic 12-TMC ligand but with an open chain structure, Scheme 15. They have compared the reactivity of nickel(III)-peroxo intermediates of both Me6-trien and 12-TMC ligands and found that open-chain nickel(III)-peroxo complex is more reactive than the macrocyclic analogue towards aldehyde deformylation.…”
Section: Aldehyde Deformylation By Biomimetic Ni 2+ Complexesmentioning
confidence: 99%